Esomeprazole magnesium enteric-coated pellet-based tablets with high acid tolerance and good compressibility - Liu, Jiang Yan; Zhang, Xiao Xue; Huang, Hao Yan; Lee, Beom Jin; Cui, Jing Hao; Cao, Qing Ri (Journal of Pharmaceutical Investigation, 2018)
The aim of this study was to develop esomeprazole magnesium (EMZ-Mg) enteric-coated pellets and pellet-based tablets, as well as to investigate the effects of pellet size and compression method on acid tolerance, content uniformity, compressibility, and stability of preparations. This study used two types of pellet cores, namely, microcrystalline cellulose (MCC) core with a particle size of 150–300 μm and sucrose core with a particle size of 600–700 μm. Enteric-coated pellets, which consisted of a drug-free core, a drug layer, a sub-coating layer (hydroxypropyl methylcellulose, 6 cps), and an enteric-coating layer (Eudragit®L30D-55), were prepared by using a bottom-spray fluidized bed-coating technique. Pellet-based tablets were prepared by using a direct compression method or a wet granulation method. The acid tolerances of the two types of enteric-coated pellets (MCC and sucrose cores) reached up to 98% in simulated gastric fluid (pH 1.0) within 2 h, and the dissolution rates in simulated intestinal fluid (pH 6.8) reached up to 85% of the labeled amount within 15 min. When compressed into tablets, the pellets based on MCC core (smaller particle size) displayed a significantly higher acid tolerance (up to 92%) compared with the pellets based on sucrose core (larger particle size). In addition, the MCC core-based tablets (F8), especially those prepared by using a granulation method, showed higher drug content uniformity and compressibility than the sucrose core-based tablets (F10), and no lamination phenomenon was observed during compression. The crystallinity of EMZ-Mg was altered during drug layering process, and some physicochemical interactions were observed between the drug and excipients. Moreover, the two types of enteric-coated pellets showed a relatively high stability after storage under high temperature and strong light. However, they showed poor stability under high humidity, resulting in remarkable degradation of active compound. The EMZ-Mg enteric-coated pellets and pellet-based tablets were successfully developed, and reduction in pellet size and wet granulation reduced the differences in content uniformity and better protected the pellet coating from damages during compression.
Keywords: Acid tolerance; Content uniformity; Enteric-coated pellets; Esomeprazole magnesium; Pellet loaded tablets